Examining how social networks influence women and under-represented minority students' pursuit of engineering in university: when, who, and how? - Hesborn Wao; Gladis Kersaint; Chrystal A. S. Smith; Rebecca Campbell-Montalvo; Ellen Puccia; John Skvoretz; Julie P. Martin; Reginald Lee; George MacDonald (SpringerOpen, 2023)
Abstract Background Women and under-represented minority (URM) students continue to be under-represented in STEM and earn the lowest proportion of undergraduate engineering degrees. We employed a mixed methods research approach grounded in social capital theory to investigate when they first consider pursuing engineering as a college degree major, who influences this decision, and how the influence occurs. First, we surveyed 2186 first-year undergraduate students entering engineering programs at 11 universities in the U.S. during the fall of 2014. Next, we interviewed a subsample of 55 women and URM students. Results Survey findings indicated that women were more likely than men to consider pursuing engineering while in high school, before admission into college, or while in college rather than considering it earlier in their education. Black and Latinx students were more likely than white students to consider pursuing engineering after high school. In addition, Black and Latinx students were more likely than white students to identify a school counselor (rather than a family member) as having the most influence on their engineering academic and career decisions. In interviews, women and URM students provided examples of influential people who connected their aptitude and enthusiasm for mathematics, science, and problem-solving to engineering, explained the benefits of being an engineer, and provided advice about engineering academic and career pathways. Conclusions Encouraging earlier consideration of engineering majors, such as during middle school, could allow women and URM students time to take requisite courses and take advantage of college preparatory programming. Likewise, universities can engage in intentional efforts to identify women and URM students with engineering interests and provide guidance. Such efforts should also include connecting them with other women and URM students in engineering. In addition, universities should support K-12 and university personnel in offering advice that can influence students' decision to declare an engineering major, which could help recruit more women and URM students into engineering.